On a meso-elstoplastic constitutive equation witb application lo deformation-induced anisolropy of a polycrystalline aggregate (Archives of Mechanics - Test, 1996)
Based on a 3-D meso-materail model of a polycrystalline aggregate, an elastoplastic constitutive equation for finite deformation is derived. The emphasis is focused on discussing the anisotropy induced by the heterogeneity in the material properties due to a complex deformation history, as well as re-orientation of the crystals or the variation of the micro-structure due to finite deformation. The theoretical predictions are in good agreement with experimental results.